Revitalisasi Nilai-Nilai Tasawuf dalam Pendidikan Karakter Islam di Era Digital - Rahmi, Aulia; Arisnaini, Arisnaini (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2025)
Islamic education in the digital era faces various challenges, particularly in shaping students' character to develop strong moral and spiritual resilience. One approach to addressing these challenges is integrating Sufism values into the Islamic education system. This study employs a library research method by analyzing various relevant literature on the role of Sufism in character education. The findings indicate that Sufism can be an effective solution in tackling moral degradation, Islamic identity crises, and the negative influences of technology among young generations. The revitalization of Sufi values in education can be implemented through strengthening spirituality in the curriculum, adopting a holistic learning approach, and utilizing technology for da'wah and character education. Through these strategies, Islamic education not only focuses on academic aspects but also shapes students with a balance of intellectual and spiritual qualities.